Using Liposomes to Alleviate the Toxicity of Chelerythrine, a Natural PKC Inhibitor, in Treating Non-Small Cell Lung Cancer - Wang, Jiahui; Song, Yijie; Zhang, Ning; Li, Ning; Liu, Congying; Wang, Bing (Frontiers in Oncology, 2021)
Aim of the Study CHE can inhibit the proliferation of lung cancer cells and induce apoptosis. However, despite having in vivo toxicity, CHE has not been thoroughly investigated in term of its in vivo antitumor effect. The present study evaluated the antitumor effect of CHE on non-small cell lung cancer cell line HCC827. Methods The antitumor effect of CHE on HCC827 was evaluated, and its potential work mechanism was investigated. CHE long circulation liposomes (CHELPs) modified with polyethylene glycol have been optimized and characterized by in vivo pharmacokinetic studies. A HCC827 xenograft model was developed on BALB/c nude mice for the assessment of the effects of CHE and CHELP. Results CHE might inhibit HCC827 growth through the ROS/PKC-ϵ/caspase 3 pathway and glycolysis. The optimized CHELP remained stable after storage for 10 days at 4°C and exhibited sustained drug release, showing approximately one-fifteenth of the in vivo clearance rate and 86 times the absorption concentration of free drug. While increasing the bioavailability of CHE, CHELP showed a good therapeutic effect on HCC827 tumor-bearing nude mice and reduced the toxicity of the free drug, improving the safety of CHE. Conclusions CHE is a candidate drug for NSCLC, and liposomes are effective in alleviating the toxicity of CHE.